‘Does Your Heart Ache with the Truth of the Past?’: Victims and Trauma in Northern Irish Culture - Shane Alcobia-Murphy (Review of Irish Studies in Europe)
This article looks at the ways in which writers and artists have critiqued both the impetus towards prescriptive forgetting inherent within the Agreement’s rhetoric and the mechanisms put in place for dealing with the past; their focus is on those who have been occluded or ignored by the Agreement, namely those who have suffered irreparable loss or who are regarded as ‘other’ to the State.